Understanding of nursing academics about the care of adolescents who experience the hospitalization process in the light of the book Pedagogy of Freedom (Research, Society and Development, 2022)
The objective of this study was to understand how nursing students care for adolescents who experience the hospitalization process in the light of Paulo Freire's Pedagogy of Autonomy. Qualitative research, of the participative action type, based on the Research Itinerary of Paulo Freire through three stages: Thematic Investigation; Encoding and Decoding; Critical Unveiling developed in Virtual Culture Circles (CCV) with eleven academics from two Nursing courses from August to September 2020, having as inclusion criteria: having attended the Curriculum Component on Pediatrics and Hebiatrics and who are over 18 years of age , and exclusion: academics who were on leave for any reason. The research was approved by the Ethics Committee with human beings, opinion number: 4,865,968. Results: Two moments emerged: 1) limit situations that subsidized the CCV and 2) possibilities of care for hospitalized adolescents, which were subdivided into three thematic nuclei: Concept of adolescence from the (re)knowledge of oneself; (In)visibility of adolescents in health services and Differences between the stages of the human living process: childhood and adolescence. Conclusion: It was possible to perceive that the care of adolescents in the light of the Pedagogy of Autonomy can contribute to a unique care attentive to the needs of adolescents and assist in the training process of health professionals, especially nursing.